Analysis of Muzakki's Decision to Pay Zakat Seen from Income, Education, Religiosity - Busnetty, Ida; Faisal, Yusuf; Prabuwon, Anton Satria (Universitas Alma Ata, 2024)
This study aims to explain how the influence of income and education on muzaki's decision to pay zakat with religiosity as a moderating variable. The method used in this research is the quantitative method. The population in this study is muzaki in Bekasi city and district using accidental sampling technique which is taken if the selection of sample members is based on chance encounters. The sample in this study amounted to 430 respondents. The data collection method uses the survey method, namely the author distributes questionnaires directly to respondents. The data analysis technique in this study researchers used SEM PLS. The result of this study found that income has a positive and statistically significant effect on muzaki's decision to pay zakat, as well as education has a positive and statistically significant effect on muzaki's decision to pay zakat. As for the moderating variable religiosity, each weakens the relationship between income and education on Muzaki’s decision to pay zakat. This research enriches previous studies on the decision of muzaki to issue zakat from the perspective of income, education, and religiosity in the community in Bekasi City and Regency.